Prices and Factor Demand in an Endogenized Input-Output Model - Kurt Kratena (Austrian Institute of Economic Research (WIFO), 2000)
This paper combines factor demand functions and price equations derived from a Generalized Leontief cost function with the traditional input - output price model. At the first level of aggregation Generalized Leontief cost functions for the factors intermediate input and labour are set up for the manufacturing industries of the Austrian economy. These functions determine factor demand for materials and labour as well as output prices for given input prices. At the second level of aggregation the intermediate demand input is split up according to the input - output structure. There the repercussion of domestic prices on input prices as described in the traditional input - output - price model is taken into account. Model simulations reveal the link between the technical coefficients and the econometric equations for domestic prices, input prices and factor demand.
Keywords: 330; Input - output price model; Generalized Leontief cost functions; endogenous technical coefficients; Input-Output-Analyse; Faktornachfrage; Faktorpreis; Kostenfunktion; Preis; Theorie